Transfusion medicine and hemostasis : clinical and laboratory aspects - Shaz, Beth; Hillyer, Christopher D.; Abrams, Charles Samuel; Roshal, Mikhail; ScienceDirect eBooks (London : Elsevier, 2013)
The second edition of Transfusion Medicine and Hemostasis continues to be the only "pocket-size" quick reference for pathology residents and transfusion medicine fellows. It covers all topics in blood banking, transfusion medicine, and clinical and laboratory based coagulation. Short, focused chapters, organized by multiple hierarchical headings, are supplemented with up to 10 suggested reading citations. This single reference covers essentially all the topics required to meet the goals and objectives of a major program in transfusion medicine and clinical coagulation. New chapters in the coagulation testing section reflect the development of new tests available and their incorporation into clinical practice. Coverage includes essential updates on the importance of new cellular therapies, peripheral blood and bone marrow hematopoietic progenitor cells, as well as cord blood banking and regenerative medicine. The authors also examine advances in the understanding of molecular testing and pathogen reduction in two separate quality control chapters (one for blood centers and one for hospitals). Updated content covers new coagulation tests, cellular therapies, and quality control issuesEasy to use, with focused, well-defined chapters in a standardized format throughoutOffers quick "cross-reference" lists at the end of each chapter Includes lists of common abbreviations and indexes that cross reference diagnostic, clinical and therapeutic commonalities.
part I. Blood banking and transfusion medicine -- part II. Hemostasis.
Previous edition: 2009.
Includes bibliographical references and index.
Online resource; title from digital title page (ebrary, viewed on July 21, 2014).
Elsevier
Elsevier
Keywords: Hemostasis; Hemostatics; MEDICAL -- Pharmacology; Hemostasis; Hemostatics; Blood Transfusion; Hemostasis; Hematologic Diseases -- therapy; Hematologic Tests -- methods; Hematologic Tests -- methods; Electronic books